On Designing Constant-Stress Partially Accelerated Life Tests under Time-Censoring - Ismail, A.A. (Проблемы прочности, 2014)
It is not easy to obtain more failure data from products with high quality and long life at normal (use) condition. Thus, accelerated tests are needed in this respect. This paper considers the constant-stress partially accelerated life tests with type-I censoring under Weibull distribution. The maximum likelihood estimators of the model parameters are derived. Partially accelerated life tests plans are developed such that the generalized asymptotic variance of the maximum likelihood estimators of the model parameters is minimized. The plan is to specify the proportion of test units that should be allocated to run under use condition. Simulation studies are made for illustrative purposes.